A study about the universals in Ideas I - Cadena, Nathalie Barbosa de La (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
The problem of universals remains a philosophical theme not only in ontology but also in epistemology. In Husserl, there are particular universals, the noematic ‘X’, the identical, and universals stricto sensu, atemporal universal names. In this paper, I present the theme as it is analyzed by Husserl in Ideas I. In the first section, I describe the trajectory to the universals highlighting the parallelism between noese and noema. In the second section, I draw the reflection of this problem on the philosophy of language which is also affected by the noeticnoematic correspondence. In the third and last section, I show how the investigation about the universals moves in the noematic sphere, and conclude defending the possibility of reaching the universal strict sense departing from the noematic ‘X’.